2009
DOI: 10.1038/nature07956
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind as the origin of rapid reddening of asteroid surfaces

Abstract: A comparison of the laboratory reflectance spectra of meteorites with observations of asteroids revealed that the latter are much 'redder', with the spectral difference explained by 'space weathering', though the actual processes and timescales involved have remained controversial. A recent study of young asteroid families concluded that they suffered only minimal space weathering. Here we report additional observations of those families, revealing that space weathering must be a very rapid process-the final c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 29 publications
12
164
1
1
Order By: Relevance
“…The many controlling variables on the rate of changes with space weathering are poorly constrained. One evolving model for the rate of space weathering on asteroids using age estimates for family members of a few apparently recent asteroid breakups along with asteroid measured color suggest that color changes associated with space weathering may be very rapid (<10 6 yr) (Vernazza et al 2009). For Vesta, the measured crystallization ages of the HED meteorites, however, indicate that the original surface of Vesta is older than the lunar highlands (e.g., McSween et al, 2010).…”
Section: Spwe: Dawn Science Objectivesmentioning
confidence: 99%
“…The many controlling variables on the rate of changes with space weathering are poorly constrained. One evolving model for the rate of space weathering on asteroids using age estimates for family members of a few apparently recent asteroid breakups along with asteroid measured color suggest that color changes associated with space weathering may be very rapid (<10 6 yr) (Vernazza et al 2009). For Vesta, the measured crystallization ages of the HED meteorites, however, indicate that the original surface of Vesta is older than the lunar highlands (e.g., McSween et al, 2010).…”
Section: Spwe: Dawn Science Objectivesmentioning
confidence: 99%
“…This model for the space weathering effects, which we applied to our data, describes the effects of solar-wind ion irradiation. This is not the only active weathering process, but it seems to be the most efficient at 1 AU (Vernazza et al 2009;Brunetto et al 2006).…”
Section: Methods Used To Analyze Datamentioning
confidence: 99%
“…Space weathering processes can explain the spectral differences between the ordinary chondrite meteorites and their presumed parent bodies -the S-type asteroids (Pieters et al 2000). Vernazza et al (2009) demonstrate the necessity to take the composition into account when evaluating weathering effectiveness. The laboratory experiments show that solarwind ion implantation is the most rapid of several competing processes (Brunetto et al 2006;Vernazza et al 2009;Loeffler et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, analysis of depth of the ∼0.95 µm absorption band, indicating degree of space weathering, revealed an evolved surface similar to that of old S-type asteroids. This either implies that space weathering is a fast process (Vernazza et al 2009), or it could also imply that the largest remnant in the family reaccumulated most of dust contained in the regolith of the parent body (see Polishook et al 2014, for comparison). In the previous paper from our group ), we reported numerous photometric observations of the largest member (1270) Datura that allowed us to resolve its rotation state and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Not only it contains the largest number of members, but its location in the innermost part of the asteroid belt promises a good outlook for obtaining observational data with even small telescopes available to our group. Mothé-Diniz & Nesvorný (2008) and Vernazza et al (2009) used spectral observations and found that members of the Datura family could be classified either Sk, Sq or even Q types. The affinity to Sq and Q sub-class is interesting as it may fit the young exposed surfaces of the family members.…”
Section: Introductionmentioning
confidence: 99%